Biodistribution, Clearance, and Long‐Term Fate of Clinically Relevant Nanomaterials. Issue 19 (1st February 2018) - Bourquin, Joël; Milosevic, Ana; Hauser, Daniel; Lehner, Roman; Blank, Fabian; Petri‐Fink, Alke; Rothen‐Rutishauser, Barbara
Abstract: Realization of the immense potential of nanomaterials for biomedical applications will require a thorough understanding of how they interact with cells, tissues, and organs. There is evidence that, depending on their physicochemical properties and subsequent interactions, nanomaterials are indeed taken up by cells. However, the subsequent release and/or intracellular degradation of the materials, transfer to other cells, and/or translocation across tissue barriers are still poorly understood. The involvement of these cellular clearance mechanisms strongly influences the long‐term fate of used nanomaterials, especially if one also considers repeated exposure. Several nanomaterials, such as liposomes and iron oxide, gold, or silica nanoparticles, are already approved by the American Food and Drug Administration for clinical trials; however, there is still a huge gap of knowledge concerning their fate in the body. Herein, clinically relevant nanomaterials, their possible modes of exposure, as well as the biological barriers they must overcome to be effective are reviewed. Furthermore, the biodistribution and kinetics of nanomaterials and their modes of clearance are discussed, knowledge of the long‐term fates of a selection of nanomaterials is summarized, and the critical points that must be considered for future research are addressed. Abstract : Understanding the long‐term fate of biomedical nanomaterials is important for the safe‐by‐design approach to bring these promising systems to the clinic. The current knowledge regarding how the exposure route can affect the biodistribution of various clinically relevant nanomaterials, and thus their interaction with cells, tissues, and organs, is reviewed, with an emphasis on prolonged exposures.